Respostas
respondido por:
0
5t + 9 = -6
5t = 3
t =
5t = 3
t =
respondido por:
0
5t + 9 = -6
5t + 9 + 6 = 0 (usa a fórmula de bhaskara ou cálculo mental)
a= 5, b= 9, c= 6
∆= (5)² - 4. (9). (6)
∆= + 25 - 216
∆= - 191
termina aqui pois o delta é negativo.
5t + 9 + 6 = 0 (usa a fórmula de bhaskara ou cálculo mental)
a= 5, b= 9, c= 6
∆= (5)² - 4. (9). (6)
∆= + 25 - 216
∆= - 191
termina aqui pois o delta é negativo.
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás